2016
DOI: 10.3390/polym8040111
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent BAPAD Dendrimeric Antigens Are Efficiently Internalized by Human Dendritic Cells

Abstract: A new fluorescent dendrimeric antigen (DeAn) based on a dendron with amoxicilloyl terminal groups was synthesized. The synthesis was carried out using a novel class of all-aliphatic polyamide dendrimer (BisAminoalkylPolyAmide Dendrimers, or BAPAD) involving the direct condensation of 3,3′-diazidopivalic acid as a building block. Iterative azide reduction/amide formation increases the dendrimer generation. The BAPAD dendrimer was designed with a cystamine core. Reduction of the disulfide bond allows the incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Results revealed these dendrons to be non-toxic and they could be easily internalized by dendritic cells. It was concluded that BAPAD dendrons could serve as efficient candidates for synthetic scaffolds for such applications [53]. Thus, dendrimers have emerged as one of the promising technique for specific delivery of antigens.…”
Section: Dendrimers As Antigen Carriersmentioning
confidence: 99%
“…Results revealed these dendrons to be non-toxic and they could be easily internalized by dendritic cells. It was concluded that BAPAD dendrons could serve as efficient candidates for synthetic scaffolds for such applications [53]. Thus, dendrimers have emerged as one of the promising technique for specific delivery of antigens.…”
Section: Dendrimers As Antigen Carriersmentioning
confidence: 99%
“…Thus, dendrons based on this structure were used as platforms in diagnosis tests of allergic reactions to drugs. 24 The dendritic moieties have also been used as scaffolds for the covalent immobilization of bioactive peptides in titanium disks, increasing the biocompatibility of oral titanium implants. 25 Furthermore, the insertion of these dendritic scaffolds into Pt(II) complexes endows them with unique properties such as aqueous solubility, shielding from quenching by dioxygen, and binding to bacterial surfaces, opening the way for the development of new phosphorescent biomarkers with promising properties.…”
Section: Introductionmentioning
confidence: 99%
“…Using a divergent approach, this novel polyamide dendrimer (BAPAD) was synthetized based on a 3,3′-diaminopivalic acid scaffold . Their excellent stability allowed the use of such dendrimers for different bio-applications. , However, despite the versatility of the system, the maximum generation of the amino terminal dendrimer obtained was generation 3, which contains 16 peripheral amino groups. , This could be explained by a dramatic decrease in the reactivity of the azide groups caused by a backfolding of these surface groups. This effect has been previously observed and is more pronounced when the synthesis of the dendrimer is performed in a divergent way .…”
Section: Introductionmentioning
confidence: 99%
“…16 Their excellent stability allowed the use of such dendrimers for different bio-applications. 17,18 However, despite the versatility of the system, the maximum generation of the amino terminal dendrimer obtained was generation 3, which contains 16 peripheral amino groups. 16,19 This could be explained by a dramatic decrease in the reactivity of the azide groups caused by a backfolding of these surface groups.…”
Section: ■ Introductionmentioning
confidence: 99%